2021
DOI: 10.1016/j.xphs.2020.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Microscopy: Particle Size/Shape Characterization, Addressing Common Errors Using ‘Analytics Continuum’ Approach

Abstract: Particle size/shape characterization of active pharmaceutical ingredient (API) is integral to successful product development. It is more of a correlative property than a decision-making measure. Though microscopy is the only technique that provides a direct measure of particle properties, it is neglected for reasons like non-repeatability and non-reproducibility which is often attributed to a) fundamental error, b) segregation error, c) human error, d) sample randomness, e) sample representativeness etc. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Also, the estimation of particle diameter is not precise, which results in high errors and deviations. The number of investigated particles is significantly lower in comparison with other methods, which makes data statistically poor [ 30 ]. As an advantage of manual measurement is no need for special software and D eff may be simply estimated by various available photo redactors.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the estimation of particle diameter is not precise, which results in high errors and deviations. The number of investigated particles is significantly lower in comparison with other methods, which makes data statistically poor [ 30 ]. As an advantage of manual measurement is no need for special software and D eff may be simply estimated by various available photo redactors.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the data is non-normal, non-linear, inhomogeneity in variance/ heteroscedasticity. That is NIR BU data were found to have violations of parametric assumptions [43,44]. On the other hand, no outliers were identified.…”
Section: Data Quality Metricsmentioning
confidence: 93%
“…When k = 1, it is leave one out cross-validation (LOOCV). Bootstrapping is a statistical process that creates several simulated samples by resampling a single dataset with replacement [43,53]. Those instances that were not resampled are used in the test set.…”
Section: Internal Validation-sensitivity Analysis (Cross-validation Andmentioning
confidence: 99%
See 2 more Smart Citations